Intranasal Immunization With a c-di-GMP-Adjuvanted Acellular Pertussis Vaccine Provides Superior Immunity Against Bordetella pertussis in a Mouse Model - Jiang, Wenwen; Wang, Xiaoyu; Su, Yuhao; Cai, Lukui; Li, Jingyan; Liang, Jiangli; Gu, Qin; Sun, Mingbo; Shi, Li (Frontiers in Immunology, 2022)
Pertussis, caused by the gram-negative bacterium Bordetella pertussis, is a highly contagious respiratory disease. Intranasal vaccination is an ideal strategy to prevent pertussis, as the nasal mucosa represents the first-line barrier to B. pertussis infection. The current intramuscular acellular pertussis (aP) vaccines elicit strong antibody and Th2-biased responses but not necessary cellular and mucosal immunity. Here, we formulated two cyclic dinucleotide (CDN)-adjuvanted aP subunit vaccines, a mammalian 2’,3’-cGAMP-adjuvanted aP vaccine and a bacterial-derived c-di-GMP-adjuvanted aP vaccine, and evaluated their immunogenicity in a mouse model. We found that the aP vaccine alone delivered intranasally (IN) induced moderate systemic and mucosal humoral immunity but weak cellular immunity, whereas the alum-adjuvanted aP vaccine administered intraperitoneally elicited higher Th2 and systemic humoral immune responses but weaker Th1 and Th17 and mucosal immune responses. In contrast, both CDN-adjuvanted aP vaccines administered via the IN route induced robust humoral and cellular immunity systemically and mucosally. Furthermore, the c-di-GMP-adjuvanted aP vaccine generated better antibody production and stronger Th1 and Th17 responses than the 2′,3′-cGAMP-adjuvanted aP vaccine. In addition, following B. pertussis challenge, the group of mice that received IN immunization with the c-di-GMP-adjuvanted aP vaccine showed better protection than all other groups of vaccinated mice, with decreased inflammatory cell infiltration in the lung and reduced bacterial burden in both the upper and lower respiratory tracts. In summary, the c-di-GMP-adjuvanted aP vaccine can elicit a multifaceted potent immune response resulting in robust bacterial clearance in the respiratory tract, which indicates that c-di-GMP can serve as a potential mucosal adjuvant for the pertussis vaccine.